Vol 1 Maret 2023 MEMBANGUN LITERASI KEUANGAN DAN INVESTASI SYARI'AH: INVESTASI SYARIAH DALAM MENDORONG PERTUMBUHAN EKONOMI PADA SEKTOR NON RILL - Rifatul Muna (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2023)
Investment in general is to invest or place assets, both in the form of assets and funds, in something that is expected to provide income or will increase its value in the future. investing is investing or placing assets, either in the form of assets or funds, in something that is expected to generate income or increase its value in the future. The formulation of the problem of this research is what is the role of sharia investment in driving economic growth in the non-real sector. The aim of this research is to find out the potential of Islamic investment in encouraging economic growth in the non-real sector. This study uses qualitative research with descriptive research types, then for the subject in this study is Islamic investment, in collecting data using methods, observation, and documentation. The results of this study indicate that the development of Islamic investment has increased the demand for Islamic investment. the large number of requests from foreign trade has had the effect of strengthening the rupiah exchange rate against the US dollar, by strengthening the value of coal, gold, silver and other new mines.